Mitochondrial COI Haplotype Diversity of Rhynchobatus australiae Collected from Ketapang Fish Port, Bangka Belitung Islands - Novita Permata Putri; Irwani Irwani; Munasik Munasik; Ranny Ramadhani Yuneni; Faqih Akbar Alghozali; Angka Mahardini (Marine Science Department Diponegoro University, 2022)
Rhynchobatus australiae is a member of the Rhinidae family and can be found in the Indo Pacific. This species is categorized as Critically Endangered according to The International Union for Conservation of Nature and Natural Resources (IUCN) Red List and listed as Appendix II Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), due to population declines. Sustainable fisheries management is urgently needed. Information related to genetic diversity is one of the most important aspects of information for appropriate sustainable fisheries management. Therefore, this research aims to investigate the genetic diversity of Rhynchobatus australiae collected from Ketapang Fish Port Bangka Belitung Islands. Total 21 samples were collected at Ketapang Fish Port. DNA extraction was carried out using the 10% chelex method and amplification was done through PCR method on the mitochondrial DNA using Fish BCL and Fish BCH primer. Sequences in size of 653 base pairs were successfully obtained from all fish samples showing the existence of 2 clades from the construction of the phylogeny tree with close genetic distance. Results showed high haplotype diversity (Hd: 0.733 ± 0.082) and low nucleotide diversity (π: 0.00176± 0.00036) with 6 polymorphic sites (S) from 7 unique haplotypes (h). This research provides basic information of genetic diversity of Rhynchobatus australiae collected from Ketapang Fish Port and complements other information to better understand the status of the threatened Rhynchobatus australiae population.